Bioequivalence of China- and Germany-manufactured bisoprolol (Concor®) tablets in fasted and fed healthy Chinese participants: a randomized, open-label, two-way, crossover study - Yin, Hang; Jin, Zhili; Li, Ran; Li, Dandan; Wang, Lusha; Dong, Ruihua (Frontiers in Pharmacology, 2025)
BackgroundThe bioequivalence of Concor® (Merck Healthcare KGaA, Darmstadt, Germany), a bisoprolol-containing tablet, manufactured in China and Concor® tablets manufactured in Germany has not been previously reported.MethodsThis single-center, open-label, randomized, two-period, two-sequence, crossover trial (28 February 2023–19 May 2023) compared the pharmacokinetics and safety of bisoprolol 5-mg tablets manufactured in China (test product) with those of bisoprolol 5-mg tablets manufactured in Germany (reference product) in healthy Chinese adults under fasted and fed conditions. Primary endpoints were Cmax, AUC0–tlast, and AUC0–∞.ResultThe mean (coefficient of variation percentage) Cmax in the fasted group was 21.2 (15.0) ng/mL (test product) and 22.1 (17.0) ng/mL (reference product). Under fed conditions, the respective Cmax values were 22.7 (18.8) ng/mL and 22.8 (15.2) ng/mL. The mean and coefficient of variation percentage for AUC were also similar between the two products. The geometric least squares mean ratio (90% confidence interval) for the test/reference product was 0.9565 (0.9006–1.0158) ng/mL for Cmax, 0.9761 (0.9370–1.0168) h·ng/mL for AUC0–tlast, and 0.9807 (0.9429–1.0200) h·ng/mL for AUC0–∞ in fasted conditions and 0.9966 (0.9289–1.0691) ng/mL for Cmax, 0.9672 (0.9220–1.0145) h·ng/mL for AUC0–tlast, and 0.9693 (0.9253–1.0155) h·ng/mL for AUC0–∞ in fed conditions, which met the pre-defined criteria for bioequivalence. No serious treatment-emergent adverse events or deaths were observed.ConclusionThis study compared the bioequivalence of bisoprolol 5-mg tablets manufactured in China to that of the tablets manufactured in Germany among healthy Chinese adults.Systematic Review Registrationidentifier CTR20230391